Two-year intermittent exposure of a multiwalled carbon nanotube by intratracheal instillation induces lung tumors and pleural mesotheliomas in F344 rats - Motoki Hojo; Ai Maeno; Yoshimitsu Sakamoto; Aya Ohnuki; Yukie Tada; Yukio Yamamoto; Kiyomi Ikushima; Ryota Inaba; Jin Suzuki; Yuhji Taquahashi; Satoshi Yokota; Norihiro Kobayashi; et al. (Particle and Fibre Toxicology, 2022)
Abstract Background A mounting number of studies have been documenting the carcinogenic potential of multiwalled carbon nanotubes (MWCNTs); however, only a few studies have evaluated the pulmonary carcinogenicity of MWCNTs in vivo. A 2-year inhalation study demonstrated that MWNT-7, a widely used MWCNT, was a pulmonary carcinogen in rats. In another 2-year study, rats administered MWNT-7 by intratracheal instillation at the beginning of the experimental period developed pleural mesotheliomas but not lung tumors. To obtain data more comparable with rats exposed to MWNT-7 by inhalation, we administered MWNT-7 to F344 rats by intratracheal instillation once every 4-weeks over the course of 2 years at 0, 0.125, and 0.5 mg/kg body weight, allowing lung burdens of MWNT-7 to increase over the entire experimental period, similar to the inhalation study. Results Absolute and relative lung weights were significantly elevated in both MWNT-7-treated groups. Dose- and time-dependent toxic effects in the lung and pleura, such as inflammatory, fibrotic, and hyperplastic lesions, were found in both treated groups. The incidences of lung carcinomas, lung adenomas, and pleural mesotheliomas were significantly increased in the high-dose group compared with the control group. The pleural mesotheliomas developed mainly at the mediastinum. No MWNT-7-related neoplastic lesions were noted in the other organs. Cytological and biochemical parameters of the bronchoalveolar lavage fluid (BALF) were elevated in both treated groups. The lung burden of MWNT-7 was dose- and time-dependent, and at the terminal necropsy, the average value was 0.9 and 3.6 mg/lung in the low-dose and high-dose groups, respectively. The number of fibers in the pleural cavity was also dose- and time-dependent. Conclusions Repeated administration of MWNT-7 by intratracheal instillation over the 2 years indicates that MWNT-7 is carcinogenic to both the lung and pleura of rats, which differs from the results of the 2 carcinogenicity tests by inhalation or intratracheal instillation.